Pelatihan Penggunaan Alat Ukur Fisika Dasar untuk Meningkatkan Pemahaman Siswa SMAN 1 Kurik - Wilfrida Mayasti Obina; Tutik Yuliatun; Selestina Kostaria Jua; Algiranto Algiranto; Aprilita Ekasari; Evani Doana Nababan; Kristina Uskenat; Merta Simbolon (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
The use of basic physics measuring instruments is a crucial skill that students must master, as it will serve as the foundation for using more advanced physics measuring instruments and future technologies. However, the limited frequency of laboratory sessions often hinders students’ practical understanding. This community service activity aims to improve 12th-grade science students' understanding at SMA Negeri 1 Kurik, South Papua, of how to use basic physics measuring instruments, including vernier calipers, micrometers, Ohaus balances, and optical instruments. The methods used in this training include presentations on measurement concepts, demonstrations of instrument use, and direct group-based practical guidance. Improvements in students' understanding were evaluated using pre- and post-tests. The analysis results showed a highly significant increase in student understanding, with the average initial understanding score rising from 26.6% on the pre-test to 98.85% on the post-test. Based on these results, it can be concluded that hands-on learning helps hone psychomotor skills and strengthen students’ conceptual understanding of accuracy and the analysis of physics measurement results.